Disruptive, impulse control and conduct disordered behaviours in schools : a multisystemic intervention using rational emotive behaviour therapy - Visser, M.J. (Maretha Johanna) (University of Pretoria, 2022)
Thesis (PhD (Psychology))--University of Pretoria, 2022.